Corporate Sustainable Business Practices And Organizational Attractiveness Among Professionals In Malaysia - Magbool, Mohamad Abu Huzaifah (2012)
It is an article of faith that talented workforce is essential for differentiating an organization from its rivals. As human resources are mostly unique, non-imitable, and non-substitutable it has been recommended as a newly minted strategy to enable organization to achieve not only competitive advantage rather sustainable competitive advantage. However, this valuable resource as all other valuable resources in this earth is finite. Thus a war is being raged in pursuit of the talented workforce. Drawing on social identity theory and signalling theory, the researcher hypothesizes that organizations can leverage on their sustainable business practices to attract valuable talent in order to gain competitive advantage. Corporate sustainable business (CSB) practices creates a positive image for an organization and social identity theory suggests that individuals are attracted to this positive image of the organization to fulfil their self-esteem.